STRATEGI MANAJEMEN PERUBAHAN DALAM MENINGKATKAN DISPLIN PEGAWAI DI DINAS PEMBERDAYAAN MASYARAKAT DESA KABUPATEN NIAS UTARA - Tulus Hati Gea; Odaligoziduhu Halawa; Syah Abadi Mendrofa; Fatolosa Hulu (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to formulate change management strategies to improve employee discipline at the Community and Village Empowerment Office (DPMD) of North Nias Regency. The background of the research is based on the condition of weak employee discipline, as reflected in high levels of tardiness, low participation, and minimal responsibility in completing tasks. These issues stem from the suboptimal implementation of change management strategies, the weak role of leaders as agents of change, and the lack of coordination and cross-departmental communication. This research uses a descriptive qualitative approach with a case study method, involving data collection through observation, interviews, and documentation. The analysis was conducted to identify obstacles, the need for change, and the role of leadership in building an adaptive work culture. The results show that improving employee discipline requires an integrated change strategy, including the formulation of adaptive internal policies, capacity building through continuous training, strengthening organizational communication, and implementing a fair and consistent reward and punishment system. The implementation of this strategy is expected to improve internal management systems, encourage employee engagement, and foster a professional and responsible work culture.